Lupus vulgaris of the auricle - Hojat Eftekhari; Rafiei Rana; Daryakar Arash; Mohammad Hosseini Maryam; Naji Rad Sara (Our Dermatology Online, 2017)
Nowadays despite decrease in the tuberculosis (TB) incidence around the world with standard anti tubercular treatment, atypical forms of TB is increasing due to extensive use of immunosuppressive therapy for autoimmune diseases and increasing prevalence of HIV infection, so early diagnosis of pulmonary and extra pulmonary TB in these patients is very important. Cutaneous TB could be a great imitator and confused with other granulomatous lesions. It has different morphological patterns. Lupus vulgaris (LV) is the most common type of cutaneous TB which usually involves head and neck. We present herein a case of LV in auricular region without apparent systemic involvement.